Formulation and evaluation of syrup containing medicinal materials in Shi Quan Da Bu Tang - Ha, Kim Phượng; Huynh, Lời (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Thập Toàn Đại Bổ Thang (Sipjeondaebo-tang, Ten Inclusive Great Tonifying Decoction) has been used for treatment of both qi and blood deficiency syndromes. It is also commonly employed in the management of chronic fatigue syndrome. This study aimed to formulate and evaluate a syrup containing ten tonifying herbs. The formulation consisted of ten medicinal herbs including Radix Codonopsis pilosulae (150 g); Rhizoma Atractylodes macrocephalae (100 g); Poria cocos (80 g); Radix Glycyrrhizae (80 g); Radix Angelicae sinensis (100 g); Rhizoma Ligustici wallichii (80 g); Radix Paeoniae lactiflorae (100 g); Radix Rehmanniae glutinosae praeparata (150 g); Radix Astragali membranacei (150 g); Cortex Cinnamomi (100 g). The herbs were extracted using hot water to get extract which was concentrated to obtain liquid extract. The sweetening agent used was an extract from Stevia rebaudina. A total of 1.09 kg of raw materials was extracted, yielding 1.09 kg of aqueous extract, which was then combined with Stevia rebaudina extract to produce the syrup. The syrup was evaluated in accordance with the Vietnamese Pharmacopoeia V. The herbal syrup was successfully formulated and assessed, demonstrating its potential as an alternative medicine for treatment of fatigue.